Gender, Region, and Field of Expertise in Vocational Education: A Map of Inequality among Vocational High School Students - Agustina Multi Purnomo; R. Siti Pupu Fauziah; Martin Roestamy; Abraham Yazdi Martin; Helmia Tasti Adri; Maura Najwa Noor Raina Tirta (ASEAN Journal of Educational Research and Technology, 2025)
This study maps and analyzes inequalities in vocational field of expertise choices among Indonesian vocational school students by gender and region. The research employed descriptive quantitative methods, including the Chi-square Test, Analysis of Variance (ANOVA), Heatmaps, Decision Tree Classifiers, Lasso Regression, and Quartiles. The research data were vocational school data in 39 regions and vocational school students in 2023. Gender differences influenced the choice of area of expertise in vocational schools. There were areas of expertise in the male domain or the female domain. The region categorization did not influence the number of male and female students or the choice of field of expertise. These results were due to a gendered distribution across vocational fields arising from social norms and peer-composition signals rather than from a regional inequality context. This research is poised to significantly influence policies that promote equitable gender representation among students in vocational fields at vocational schools.